Dydaktyka kultury a podejście ukierunkowane na działanie w nauczaniu języka polskiego jako obcego - Marzena Baran (Postscriptum Polonistyczne)
The aim of the article is to discuss the possibilities of using the concept of taskbased teaching and its methodology to improve intercultural competencies of people learning Polish as a foreign language. The author of the article claims that such methods and strategies within CERF can be extremely effective in improving intercultural competencies. The article concludes with a list of tasks suggested by the author as suitable to achieve this goal.